Design And Analysis Of Electrical Iron Using Boothroyd Dewhurst DFMA Methodology - Mohd Hazuan , Mohd Zawawi (UTeM, 2009)
The objective of this project is to analyze an existing design of a selected electrical iron and to produce a new design and analyze it using the Boothroyd Dewhurst DFMA method. The new design will contain less parts, hence reducing the cost, assembly time and operation. In order to get to the objective, any information about electrical iron were gathered to get a better insight on how the iron works. Information about software such as CATIA and Boothroyd Dewhurst will also be gathered. These information may come from books, journals, the internet, newspapers and the library.